2021
DOI: 10.1530/eje-21-0553
|View full text |Cite
|
Sign up to set email alerts
|

MECHANISMS IN ENDOCRINOLOGY: Local and systemic effects of glucocorticoids on metabolism: new lessons from animal models

Abstract: Glucocorticoids regulate a remarkable variety of essential functions, including development, immunomodulation, maintenance of circadian rhythm and the response to stress. Glucocorticoids acutely increase energy availability; this is accomplished not only by mobilizing energy stores, but also by diverting energy away from anabolic processes in tissues such as skeletal muscle and bone. While this metabolic shift is advantageous in the short term, prolonged glucocorticoid exposure frequently results in central ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 132 publications
1
15
0
Order By: Relevance
“…Corticosteroid hormones (CHs) are critical to transitioning amphibian tadpoles into metamorphosis (23), while FV3 encodes a b-hydroxysteroid dehydrogenase homolog (52L), which is thought to be important to viral immune evasion (24). Hydroxysteroid dehydrogenase enzymes are typically involved in steroid biosynthesis and metabolism (25). Because our findings indicated antiviral protection of tadpole kidneys decreased with onset of metamorphosis, we reasoned that the FV3 52L confers evasion of host immunity by promoting metamorphosis.…”
Section: Resultsmentioning
confidence: 98%
“…Corticosteroid hormones (CHs) are critical to transitioning amphibian tadpoles into metamorphosis (23), while FV3 encodes a b-hydroxysteroid dehydrogenase homolog (52L), which is thought to be important to viral immune evasion (24). Hydroxysteroid dehydrogenase enzymes are typically involved in steroid biosynthesis and metabolism (25). Because our findings indicated antiviral protection of tadpole kidneys decreased with onset of metamorphosis, we reasoned that the FV3 52L confers evasion of host immunity by promoting metamorphosis.…”
Section: Resultsmentioning
confidence: 98%
“…All protocols described were approved by the Committee of Ethics in the Use of Animals of the Institute of Biomedical Sciences, University of Sao Paulo (CEUA-ICB/USP #89/2016; #26/2017; 9535190219). For the experiments, SPF-certified 8 weeks old male Wistar Hannover rats obtained from the Institute of Biomedical Sciences Animal Facility were used, since sex could be an important variable in adipose tissue analyzes [ 36 ]. Each rat was housed in an individual open polycarbonate cage (model 1291H, 425 × 266 × 185 mm and 800 cm 2 of floor area, Tecniplast ® , Buguggiate, VA, Itália Italy) in our laboratory private room at Animal Care of the Department of Physiology and Biophysics for 4 weeks of acclimatization to the new space, light cycle, and human–rat bond before the treatment protocol starts.…”
Section: Methodsmentioning
confidence: 99%
“…27 Further study showed an acute (36-hour) GC exposure in male human subjects increases UCP1 protein levels and brown adipose tissue thermogenic activity, whereas chronic GC exposure (at least two weeks) decreases brown adipose tissue activation. 28,29 Mice treated with corticosterone for four weeks showed marked lipid accumulation in brown adipose tissue and an 8% decrease in UCP1 protein expression. 30…”
Section: Effects Of Gc Excess On Adipose Tissuementioning
confidence: 99%